Integration of Unplugged Coding and Play-Based Learning in Daily Routine Activities to Develop Computational Thinking in Early Childhood - David Triatna; Narendradewi Kusumastuti (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2026)
Developing computational thinking during early childhood requires learning experiences that are meaningful, engaging, and aligned with children's developmental characteristics. This study examines the use of unplugged coding integrated into play-based learning activities embedded within children's daily classroom routines at TK Piri Yogyakarta. A qualitative phenomenological design was adopted to capture the experiences of teachers and children during the implementation of this learning approach. The participants consisted of two early childhood teachers and eighteen children aged 5–6 years. Data were gathered through direct classroom observations, interviews with teachers, and analysis of supporting documents. The collected data were analyzed using Interpretative Phenomenological Analysis (IPA) to identify common patterns across participants' experiences. The findings indicate that incorporating unplugged coding into everyday play activities provides opportunities for children to develop essential components of computational thinking, including sequencing, pattern recognition through repeated actions, and simple decision-making based on cause-and-effect situations. The learning process also promoted active participation, collaborative interaction, and greater confidence among the children because the activities were closely connected to familiar daily experiences. These findings suggest that integrating unplugged coding into routine play activities offers a practical and child-centered approach for introducing computational thinking in early childhood education.